QoS preference-aware replica selection strategy in cloud computing - XIONG Run-qun; LUO Jun-zhou; SONG Ai-bo; JIN Jia-hui (Tongxin xuebao)
A QoS preference-aware replica selection strategy for a kind of users with individual QoS sensitivity（IQS） constraints in cloud computing datacenters was put forward in advance.According to the QoS requirements of data ser-vices from IQS users,a novel three-dimensional QoS model of replica selection was introduced,and a QoS prefer-ence-aware algorithm based on analytic hierarchy process（AHP） named QoPA was proposed to deal with the IQS con-straints.In order to evaluate the replica sites in datacenters and provide the best of them to the IQS users,an algorithm for replica selection based on fuzzy comprehensive evaluation termed FCERS was designed and implemented.Results of experiments show that the FCERS can serve the various IQS users in cloud computing very well by providing reason-able replica strategies effectively.